PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Hendra Prasetyo, (2020)
The following research is a quantitative research, aimed to know the effect of good corporate governance implementation and financial performance on company value. Independent variable included in this research is independent commissioner, board of director, committe of audit and institutional ownership as a proxy of Good Corporate Governance. Return on Equity (ROE) as a proxy of Financial Performance . Tobins'Q is used for measuring company's value as an independent variabel. The sample included in this research is an state-owned enterprises of Indonesia (BUMN) within period of time 2014-2018. The Purposive Sample Method is used to choose the sample. It have been obtained 22 of BUMN all sector. The results ofsthis research indicate that the existence of an independent commissioner has no effect on firm value, the audit committe has no effect on firm value and ROE has no effect on firm value. The board of directors has a negative effect on company value and institutional ownership has a positive effect on company value.